Metallic antiferromagnets - Siddiqui, Saima A.; Sklenar, Joseph; Kang, Kisung; Gilbert, Matthew J.; Schleife, André; Mason, Nadya; Hoffmann, Axel (Journal of applied physics, 2020)
Antiferromagnetic materials have recently gained renewed interest due to their possible use in spintronics technologies, where spin transport is the foundation of their functionalities. In that respect, metallic antiferromagnets are of particular interest since they enable complex interplays between electronic charge transport, spin, optical, and magnetization dynamics. Here, we review the phenomena where the metallic conductivity provides a unique perspective for the practical use and fundamental properties of antiferromagnetic materials. The future direction is outlined with respect to the current advances of the field.